sir please solve in detail ,,,,it is from inverse trignometric function..

Asked by  | 29th Oct, 2009, 03:38: PM

Expert Answer:

tan 1/2 [ sin-12x/1+x2 + cos-1 1-y2/1+y2 ]

since sin-12x/1+x=2 tan-1  x   and 2tan-1  y = cos-1 (1-y2/1+y2 )

tan 1/2[2 tan-1  x +2tan-1  y]= tan[tan-1 x+tan-1 y]  

using tan-1 x+tan-1 y  = tan-1 (x+y)/(1-xy)

= tan[tan-1 (x+y)/(1-xy)]=x+y/(1-xy)

Answered by  | 5th Nov, 2009, 11:40: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.